2017
DOI: 10.1038/s41598-017-05769-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential NF2 Gene Status in Sporadic Vestibular Schwannomas and its Prognostic Impact on Tumour Growth Patterns

Abstract: The great majority of sporadic vestibular schwannomas (VSs) are due to the inactivation of the NF2 gene. In this study, we found age-dependent differences in the clinical parameters of sporadic VSs. Young patients were characterized by progressive tumour behaviours, including earlier onset of initial symptoms, shorter symptom duration and larger tumour size. An increased rate of “two-hits” of both NF2 alleles, usually by mutation and allelic loss, was observed in young cases compared to older, and this correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 42 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…The methylation status of these specific sites is consistent with the expression of NF2 mRNA [37]. In VS, the methylation of the promoter-associated CpG island may be a secondary event of the inactivation of the gene in 'one-hit' tumors [17]. However, some researchers pointed out that the NF2 methylation is not a mechanism of merlin loss in schwannomas [38,39].…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…The methylation status of these specific sites is consistent with the expression of NF2 mRNA [37]. In VS, the methylation of the promoter-associated CpG island may be a secondary event of the inactivation of the gene in 'one-hit' tumors [17]. However, some researchers pointed out that the NF2 methylation is not a mechanism of merlin loss in schwannomas [38,39].…”
mentioning
confidence: 70%
“…The NF2 gene encodes for a tumor suppressor protein, which is located on chromosome 22q12.2 [16,17]. The product of the NF2 gene, which is a 595-amino acid protein called the merlin protein, acts as a mediator in signal transmission [16,18,19].…”
Section: The Normal Structure and Function Of The Nf2 Genementioning
confidence: 99%
“…40 Further, our review of the literature found the most recent study indicating a 59% incidence of NF2 genetic alterations in genomic DNA from sporadic VS with 33% demonstrating a double hit. 22 We suspect that the rate of NF2 mutations in VS is greater than 59%, and in our own experience we have found the number to approach 100% (unpublished data). Furthermore, our review of the literature found no published cases of UHGPS containing NF2 gene mutations or other frequent chromosome 22 aberrations.…”
Section: Application Of Proposed Modification To Cahan's Criteria Utimentioning
confidence: 83%
“…[17][18][19][20][21][22][23][24][25][26] Furthermore, it has been reported that 30 to 66% of VS contain a double hit knockout of the NF2 gene, either from mutations or a mix of mutation and LOH. [17][18][19][20][21][22][23][24] Conversely, previously reported cases of UHGPS have lacked such specific chromosomal aberrations or mutations in chromosome 22. In the investigation of the genetic profile of UHGPS, Lewin et al 27 and Perot et al 28 found that 22 and 71% of cases harbored a TP53 mutation on chromosome 17, respectively.…”
Section: Application Of Proposed Modification To Cahan's Criteria Utimentioning
confidence: 99%
“…Two hits inactivation of the NF2 gene, encoding merlin, leads to the development of neurofibromatosis type 2-related schwannomas. Sporadic VSs are unilateral tumours which are also considered to be related to NF2 /merlin deficiency [ 1 , 2 ]. These tumours are usually slow growing and the “wait and scan” policy is suitable for these patients.…”
Section: Introductionmentioning
confidence: 99%